Analysis of the Electromechanical Coupling Vibration of Belt Drive Mechanism when the Motor Starting - Li Gaofeng (Jixie chuandong)
Taking the differential equation of the electromechanical coupling and bending and torsion nonlinear vibration of the belt drive mechanism which establishing according to the Lagrange- Maxwell equation as research object,by using the Runge Kutta method,the nonlinear characteristic of the electromechanical coupling system and the vibration characteristic in the state of the motor starting are analyzed,the phase diagram,time response,frequency spectrum and the axis trajectory are obtained. When the motor starting,the axis trajectory has apparent change,it shows that the motor is not stable. By phase diagram shows that the influence of motor on the torsional vibration is not very obvious.